Metode Bioteknologi Tanaman Lavender (Lavandula Officinalis) Jangka Panjang Sebagai Aromaterapi Bagi Penyakit Genetik Yang Terekspresi Gen Target Level Molekular (Kajian Pustaka). - Rezaldi, Firman; Erni Suminar; Syariful Mubarok; Vevi Maritha; Roni Gumilar; Elok Zubaidah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2025)
Lavender is a plant that has various potentials to be developed in various therapeutic aspects, especially as an immunomodulator. Lavender oil is an active ingredient that has quite a lot of potential to be developed as the latest therapeutic agent where its use can be used by inhalation, aromatherapy massage, aromatherapeutic baths, and saunas. The results of metabolomic analysis from previous research results lavender contains alpha-pinene (0.44%), camphene (0.30%), beta-pinene (0.41%), beta mycene (1.11%), acetic acid (0. .74%), limonene (1.50%), cineole (4.72), linalool (36.55%), camphor (3.16%), terpinine-4-ol (2.07%), linalyl acetate (32.54), geranyl acetate (1.79%), nerly acetate (1.14%), and caryophyllene (7.55%). Thyme can decrease the production and gene expression of pro-inflammatory mediators, including Tumor Necrosis Factor-? (TNF-?), interleukin-(IL) 1B, and IL-6, and increase the marker for the anti-inflammatory cytokine IL-10. Chamomile is also used for the treatment of inflammatory diseases. Borage has gamma linoleic acid, which suppresses TNF-?. It increases prostaglandin-E levels leading to augmentation of cyclic adenosine monophosphate. Efforts need to be made to develop lavender as a herbal therapeutic in the context of modern plant biotechnology through a primordial stage (callus) tissue culture approach, biotic elicitors, and Cas-9.